Bertahan Dalam Pencobaan Menurut Yakobus 1:12-15 Dan Refleksi Teologisnya Terhadap Jemaat GKPPD Sangga Beru - Despriana Rismawati Tumangger; Bernhardt Siburian; Nurelni Limbong (Sekolah Tinggi Pastoral Kateketik Santo Fransiskus Assisi, 2025)
The aim of this research is to find out how to surviveTemptation According to James 1:12-15 and to know Reflection on surviving trials according to the letter James 1:12-15 towards the Sangga Beru GKPPD Congregation